Diretrizes multidimensionais determinantes na elaboração de planos municipais de desenvolvimento rural sustentável - Dalbello, Liliane (2023)
It was investigated how the multidimensional indicators can be used for the elaboration of a contemporary Municipal Sustainable Rural Development Plan (PMDRS), which meets the Sustainable Development Goals (SDGs). In the light of the multidimensional analysis, the research was anchored in the general objective of proposing guidelines for the elaboration of a PMDRS, based on multidimensional indicators aligned with the target of the (SDGs). When it is understood that sustainable development is a complex process and that the engaged community has skills that are articulated, they reveal actions by which they trigger the understanding of how to act for an alternative economy. Soon, social actors were mobilized, subjects of transformation of the territory they belong and their specificities, desires and potentials were sought, when methodologically worked, through the focus group, measurable variables emerged through the scrutiny of the socioeconomic, environmental and institutional dimensions, by which they gave robustness to the research. This was supported by the methodological protocol “multidimensional circuit”, a participatory approach, to identify variables at the municipal and regional scales, which during the research was adapted from the culture circuit by Paul Du Gay et al. (1997) and supported by the theoretical discussion of the path from unidimensional to multidimensional development, that is, sustainable development, as well as reflection on the territory as material and immaterial heritage that influences the new rural, the urban space. To achieve the general objective, the research unfolded in: a) Developing socioeconomic, environmental and institutional variables at the local and regional scale to propose guidelines in order to structure a management plan based on the SDGs, variables arising from the triangulation of primary data, documentary and bibliographical research; b) Align variables with SDG targets, identifying indicators for a municipal rural development plan to become sustainable; and, c) Elaborate guidelines to guide the structuring of PMDRS, with multidimensional indicators in a feasible way and evaluated with goals. Guidelines based on the pillars: Food Safety and Health; Infrastructure in the Field; Production, Distribution and Sustainable Consumption; Innovation and Quality of life; Soil, Water and Resilience; and Sustainable Integration. It was concluded that the established guidelines will guide the actions of managers in the rural environment, prioritizing sustainable rural development and enabling the use of indicators, validated academically, nationally and internationally, as fundamental tools for collecting primary data and structuring political planning in multidimensions, allowing to analyze scenarios and monitor the PMDRS. Furthermore, in this plan, the synchronicity of environmental plans and instruments at different territorial scales is essential, in addition to promoting public-private partnerships and the active participation of universities and civil society to promote sustainable development in rural and urban areas. When drawing up plans to consistently achieve the SDGs, it is necessary to use variables that are adaptable to the specific circumstances of each context in order to avoid inflexible plans, and above all, Top-down strategies, which involve only technicians and public managers, are not enough, it is crucial to incorporate Bottom-up strategies that allow the participation of the community in decision-making processes, as well as in the feedback of actions, for an effective PMDRS that envisages alternative economies. Thus, sustainable rural development is hoped for.